The influence of e-participation as antecedent on behavioural intention to use among Sarawak e-filers - Lim, Ai Ling, 1973-, author; Maslin Masrom, supervisor; Sekolah Razak UTM Dalam Kejuruteraan dan Teknologi Termaju (2015)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2015